2004
DOI: 10.1111/j.0886-0440.2004.04007.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Surgery in Diabetic Patients

Abstract: The present study suggests that diabetes increases the risk of superficial wound infections after coronary artery bypass grafting. But diabetics do not necessarily have an increased risk of major complications and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
2
6
0
2
Order By: Relevance
“…Similar to our findings, in some other studies, no significant relationship was found between diabetes and mortality [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, in some other studies, no significant relationship was found between diabetes and mortality [16,17].…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative factors associated with increased incidence of SV infection include increased age, 10,11 female sex, 9,12-14 increased body mass index, 9,10,13,[14][15][16] and comorbidities such as DM, 9,[11][12][13]17 PVD, [11][12][13] low preoperative hemoglobin levels, 14 congestive heart failure, and chronic renal failure, whereas the peroperative factors include duration of surgery, open technique of harvesting, 1,18-21 harvesting from the leg with deep vein thrombosis, inappropriate use of electrocautery, and IABP use, and these factors are modifiable.…”
Section: Risk Factors Associated With Gsvhsimentioning
confidence: 99%
“…There is also a high comorbidity between Peripheral Vascular Disease and Coronary Artery Disease (Brandt et al, 2004;Eagle et al, 1994;Hertzer et al, 1984). While several studies have reported short-term adverse outcomes in Coronary Artery Bypass Grafting patients that also have Peripheral Vascular Disease (Gersh et al, 1989;Grover et al, 1990;Higgins et al, 1992;Kunadian et al, 2007;Magovern et al, 1996;O'Connor et al, 1992;Rosenthal et al, 2003;Sutton-Tyrrell et al, 1998) the long-term outcomes have not been thoroughly investigated.…”
Section: Comorbidity With Coronary Artery Diseasementioning
confidence: 99%